Protective effects of Atractylodes macrocephala polysaccharides on acetaminophen-induced liver injury - Wu, Jiali; Jia, Biao; Gong, Shuai; Li, Yangpeng; Wang, Jiaqi; Huang, Yuqiao; Guo, Jiao (Frontiers in Pharmacology, 2025)
BackgroundDrug-induced liver injury (DILI) is a major clinical concern due to its unpredictable nature and lack of effective therapeutic options.MethodsThis study investigated the hepatoprotective effects of Atractylodes macrocephala polysaccharides (AMPs) in a mouse model of acetaminophen (APAP)-induced liver injury. Mice were pretreated with AMPs for 7 days prior to APAP challenge, and liver injury was evaluated through histopathology, serum biochemistry, molecular assays, and gut microbiota analysis.ResultsAMPs treatment significantly reduced serum alanine aminotransferase (ALT) and aspartate aminotransferase (AST) levels compared to the APAP group (p < 0.05). Hepatic oxidative stress was alleviated, as indicated by increased levels of glutathione (GSH, p < 0.05) and superoxide dismutase (SOD, p < 0.05), and reduced malondialdehyde (MDA, p < 0.05). AMPs also suppressed inflammatory cytokines, including Il-1β, Tnf-α, Il-6, and Nlrp3 (p < 0.05), and modulated apoptosis-related proteins by downregulating Bax and upregulating Bcl-2 and Bcl-xl expression (p < 0.05). Furthermore, AMPs improved gut microbiota diversity and enriched beneficial genera such as Roseburia, as revealed by 16S rDNA sequencing. Fecal microbiota transplantation from AMPs-treated mice replicated these hepatoprotective effects, highlighting the involvement of the gut–liver axis.ConclusionThese findings support the therapeutic potential of AMPs as a multifaceted agent for DILI, exerting protective effects through modulation of oxidative stress, inflammation, apoptosis, and intestinal dysbiosis.